Unravelling the infodemic: a systematic review of misinformation dynamics during the COVID-19 pandemic - Sudip Bhattacharya; Alok Singh; Alok Singh (Frontiers in Communication)
IntroductionThe COVID-19 pandemic triggered not only a public health crisis but also a parallel “infodemic”—an overwhelming flood of information, including false or misleading content. This phenomenon created confusion, mistrust, and hindered public health efforts globally. Understanding the dynamics of this infodemic is essential for improving future crisis communication and misinformation management.MethodsThis systematic review followed PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for studies published between December 2019 and December 2024. Studies were included based on predefined criteria focusing on COVID-19-related misinformation causes, spread, impacts, and mitigation strategies. Data were extracted, thematically coded, and synthesized. The quality of studies was assessed using the AMSTAR 2 tool.ResultsSeventy-six eligible studies were analyzed. Key themes identified included the amplification of misinformation via digital platforms, especially social media; psychological drivers such as cognitive biases and emotional appeals; and the role of echo chambers in sustaining false narratives. Consequences included reduced adherence to public health measures, increased vaccine hesitancy, and erosion of trust in healthcare systems. Interventions like fact-checking, digital literacy programs, AI-based moderation, and trusted messengers showed varied effectiveness, with cultural and contextual factors influencing outcomes.DiscussionThe review highlights that no single strategy suffices to address misinformation. Effective mitigation requires a multi layered approach involving reactive (fact-checking), proactive (digital literacy, community engagement), and structural (policy and algorithm transparency) interventions. The review also underscores the importance of interdisciplinary collaboration and adaptive policies tailored to specific sociocultural settings.